In the Shadow of Denali - Peterson, Tracie; Woodhouse, Kimberley 1973- (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2017)
Cassidy Ivanoff and her father, John, a wilderness guide, work at a prestigious new hotel outside Mt. McKinley. John's new apprentice, Allan Brennan, finds a friend in Cassidy, but the real reason he's there-- to learn the truth about his father's death --is far more dangerous than he knows.
Keywords: Man-woman relationships -- Fiction; Murder -- Fiction -- Investigation; Mountain resorts -- Fiction; Alaska -- Fiction; Christian fiction; Religious fiction; Historical fiction; Romance fiction